The Changes in Visual Acuity Values of Japanese School Children during the COVID-19 Pandemic - Shingo Noi; Akiko Shikano; Natsuko Imai; Fumie Tamura; Ryo Tanaka; Tetsuhiro Kidokoro; Mari Yoshinaga (MDPI AG, 2022)
The coronavirus disease 2019 (COVID-19) pandemic may result in a greater decrease in visual acuity (VA) among Japanese children. Our study aimed to examine Japanese children's VA during the pandemic. VA data were collected using standard eye tests during school health check-ups conducted in 2019 and 2020 on 5893 children, in seven public elementary schools and four public junior high schools in Tokyo, Saitama, Kanagawa, and Shizuoka. VA changes were statistically analyzed. The relationship between the survey year and poor VA yielded a significant regression coefficient for the surveyed years in elementary and junior high school students. The 2019 VA value and VA change from 2019 to 2020 demonstrated a significant regression coefficient in elementary school students with VAs of "B (0.7-0.9)" and "C (0.3-0.6)", and junior high school students with VAs of "B", "C", and "D (<0.3)". An analysis of the relationship between the survey year and eye laterality of VA yielded a significant regression coefficient in the surveyed years for elementary (OR, 1.516; 95% CI, 1.265-1.818) and junior high school students (OR, 1.423; 95% CI, 1.136-1.782). Lifestyle changes during the COVID-19 pandemic might have affected VA and eye laterality in Japanese children.